Growth and Metal Accumulation of an Alyssum murale Nickel Hyperaccumulator Ecotype Co-cropped with Alyssum montanum and Perennial Ryegrass in Serpentine Soil - Broadhurst, Catherine L.; Chaney, Rufus L. (Frontiers in Plant Science, 2016)
The genus Alyssum (Brassicaceae) contains Ni hyperaccumulators (50), many of which can achieve 30 g kg-1 Ni in dry leaf. Some Alyssum hyperaccumulators are viable candidates for commercial Ni phytoremediation and phytomining technologies. It is not known whether these species secrete organic and/or amino acids into the rhizosphere to solubilize Ni, or can make use of such acids within the soil to facilitate uptake. It has been hypothesized that in fields with mixed plant species, mobilization of metals by phytosiderophores secreted by Graminaceae plants could affect Alyssum Ni, Fe, Cu and Mn uptake. We co-cropped the Ni hyperaccumulator Alyssum murale, non-hyperaccumulator A. montanum and perennial ryegrass in a natural serpentine soil. All treatments had standard inorganic fertilization required for ryegrass growth and one treatment was compost amended. After 4 months A. murale leaves and stems contained 3600 mg kg-1 Ni which did not differ significantly with co-cropping. Overall Ni and Mn concentrations were significantly higher in A. murale than in A. montanum or L. perenne. Copper was not accumulated by either Alyssum species, but L. perenne accumulated up to 10 mg kg-1. A. montanum could not compete with either A. murale or ryegrass, and neither Alyssum species survived in the compost-amended soil. Co-cropping with ryegrass reduced Fe and Mn concentrations in A. murale but not to the extent of either increasing Ni uptake or affecting plant nutrition. The hypothesized Alyssum Ni accumulation in response to phytosiderophores secreted by co-cropped grass did not occur. Our data do not support increased mobilization of Mn by a phytosiderophore mechanism either, but the converse: mobilization of Mn by the Alyssum hyperaccumulator species significantly increased Mn levels in L. perenne. Tilling soil to maximize root penetration, adequate inorganic fertilization and appropriate plant densities are more important for developing efficient phytoremediation and phytomining approaches.